Case Report: Virtual Reality Analgesia in an Opioid Sparing Orthopedic Outpatient Clinic Setting: A Case Study - Firoozabadi, Reza; Elhaddad, Moamen; Drever, Sydney; Soltani, Maryam; Githens, Michael; Kleweno, Conor P.; Sharar, Sam R.; Patterson, David R.; Hoffman, Hunter G. (Frontiers in Virtual Reality, 2020)
Immersive virtual reality is proving effective as a non-pharmacologic analgesic for a growing number of painful medical procedures. External fixator surgical pins provide adjunctive stability to a broken pelvic bone until the bones heal back together, then pins are removed. The purpose of the present case study was to measure for the first time, whether immersive virtual reality could be used to help reduce pain and anxiety during the orthopedic process of removing external fixator pins from a conscious patient in the orthopedic outpatient clinic, and whether it is feasible to use VR in this context. Using a within-subject within wound care design with treatment order randomized, the patient had his first ex-fix pin unscrewed and removed from his healing pelvic bone while he wore a VR helmet and explored an immersive snowy 3D computer generated world, adjunctive VR. He then had his second pin removed during no VR, standard of care pain medications. The patient reported having 43% less pain intensity, 67% less time spent thinking about pain, and 43% lower anxiety during VR vs. during No VR. In addition, the patient reported that his satisfaction with pain management was improved with the use of VR. Conducting simple orthopedic procedures using oral pain pills in an outpatient setting instead of anesthesia in the operating room greatly reduces the amount of opioids used, lowers medical costs and reduces rare but real risks of expensive complications from anesthesia including oversedation, death, and post-surgical dementia. These preliminary results suggest that immersive VR merits more attention as a potentially viable adjunctive non-pharmacologic form of treatment for acute pain and anxiety during medical procedures in the orthopedic outpatient clinic. Recent multi-billion dollar investments into R and D and mass production have made inexpensive immersive virtual reality products commercially available and cost effective for medical applications. We speculate that in the future, patients may be more willing to have minor surgery procedures in the outpatient clinic, with much lower opioid doses, while fully awake, if offered adjunctive virtual reality as a non-pharmacologic analgesic during the procedure. Additional research and development is recommended.